2012
DOI: 10.4236/psych.2012.39102
|View full text |Cite
|
Sign up to set email alerts
|

Affect Consciousness and Adult Attachment

Abstract: The concept of affect consciousness refers to the ability to perceive, reflect upon, express and respond to one's own or other individuals' affective experiences. The aim of this study was to investigate how affect consciousness and adult attachment are related. Three clinical groups (eating disorders, relational problems, and stress-related problems), and one non-clinical group (total N = 82) completed the Attachment Style Questionnaire and were interviewed using the Affect Consciousness Interview-Self/Other.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Overall, evidence regarding the relationship between insecure attachment and self-consciousness is still in its infancy (e.g., Morris et al, 2014; Lech & et al, 2012). Findings of our study indicated the existence of a positive and signi cant relationship between self-consciousness and attachment styles with paranoia Meanwhile, evolutionary roots suggest that self-conscious emotions have interpersonal adaptive functions.…”
Section: Discussionsupporting
confidence: 47%
“…Overall, evidence regarding the relationship between insecure attachment and self-consciousness is still in its infancy (e.g., Morris et al, 2014; Lech & et al, 2012). Findings of our study indicated the existence of a positive and signi cant relationship between self-consciousness and attachment styles with paranoia Meanwhile, evolutionary roots suggest that self-conscious emotions have interpersonal adaptive functions.…”
Section: Discussionsupporting
confidence: 47%
“…In addition, it is unknown whether the tendency of the more avoidantly attached to touch less is conscious or not. Because they are less conscious of their affective experience (Lech et al, 2012), they might not realize that they impede touch in their relationship. Hence, a potential avenue to support people with higher attachment avoidance would be to help them be more conscious of how they create interpersonal distance.…”
Section: Discussionmentioning
confidence: 99%
“…The semistructured Affect Consciousness Interview (ACI) [ 18 ] and the self-reported Affect Integration Inventory (AII) [ 19 ] have been developed to assess the level of adaptiveness of the individual´s affect organization. Previous research has demonstrated good psychometric properties and clinical usefulness of both the ACI [ 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and the AII [ 19 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%